The Vulnerability of Correspondent Banking on Money Laundering - Sigit Handoyo (Jurnal Aplikasi Bisnis, 2017)
Bank has important role in process of converting illicit money to be legal proceeds. Once opportunity appears, money launderer will take advantage of that situation. Generally, banks which have poor anti-money laundering control become the main priority for offenders to process laundering their illicit money. These typical banks are usually high risk engaged in criminal behaviour, because they do not know whether or not their clients are engaged in money laundering activities. Offenders in other countries also use those banks as correspondent banks where they may use in transferring money. Some preventive actions have been conducted by some banks of some countries to detect the patterns of money laundering to have good anti-money laundering control, such as the US and Australia by applying advances technologies, such as data mining technologies in identifying the patterns. However, applying those technologies is not enough for preventing money laundering activities due to the inherent weaknesses on it. Thus by having good anti-money laundering control is a compulsory for banking.